2014
DOI: 10.14712/18023061.416
|View full text |Cite
|
Sign up to set email alerts
|

“Organic food is fertilised at night”: Why people (do not) buy environmentally friendly products

Abstract: The goal of this paper is to analyze barriers that discourage consumers from buying environmentally friendly products, and consequently suggest principles for effective consumer-oriented programmes of environmental education. It is based on a qualitative analysis of six focus groups (N=39) that were carried out with respondents from different consumer groups (mothers on maternity leave, pensioners, administrators, businessmen, university students, and environmental consultants). The research suggested that a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…As regards university students, the literature suggests that there are many barriers preventing consumers from buying environmentally-friendly products.Činčera et al [70], in their study with respondents from different consumer groups in the Czech Republic, found that lack of trust in the concept of sustainable consumption and consumers' personal history play an important role in consumer decision-making. More precisely, only mothers and students from the respondents' pool have explicitly expressed favorable attitudes towards sustainable consumer behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As regards university students, the literature suggests that there are many barriers preventing consumers from buying environmentally-friendly products.Činčera et al [70], in their study with respondents from different consumer groups in the Czech Republic, found that lack of trust in the concept of sustainable consumption and consumers' personal history play an important role in consumer decision-making. More precisely, only mothers and students from the respondents' pool have explicitly expressed favorable attitudes towards sustainable consumer behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study on organic food consumption values, Finch (2006) found that organic food buyers were concerned about potential declines in food quality due to the entry of large corporations into the organic food market, while non-buyers considered buying organic food based on the same corporations' ability to improve its accessibility. Cincera et al 's (2014) study of buyers and non-buyers of eco-friendly products revealed that the main reason for not buying is the lack of belief in sustainable consumption in general. In the context of fast-food consumption, Lee et al (2022) showed that non-consumers of fast food avoided it not only due to health concerns but also due to feelings of guilt associated with its consumption.…”
Section: Literature Reviewmentioning
confidence: 99%